Pola Makan Berkelanjutan: Persepsi dan Hambatan pada Generasi Muda di Bali dalam Mewujudkan Pariwisata Berkelanjutan - Wisnawa, I Made Bayu (JURNAL GASTRONOMI INDONESIA, 2025)
The increasing need for sustainable practices in the tourism industry encourages research on sustainable food consumption. The purpose of this study was to assess the perceptions, barriers and practices of sustainable eating among the younger generation in Bali, given the lack of studies exploring the socio-economic dimensions in the local context. This study used descriptive qualitative methodology with questionnaires completed by 52 respondents. Results show that the younger generation in Bali shows high awareness of sustainable diets, but still faces gaps in understanding of its relationship with sustainable tourism. While there is awareness about nutrition and support for government policies that promote access to healthy and affordable food, the lack of education about sustainable diets is a major issue. Most respondents identified an urgent need for further education and training. These results emphasise the need for integrated interventions from the government, private sector and communities to improve education and engagement of the younger generation in sustainable practices. With the potential for social transformation towards sustainability, the adoption of sustainable diets by the younger generation can strengthen Bali's position as a sustainable tourism destination.